"Moving" to a job. The role of locomotion in job search and (Re)employment. (October 2016) - Amato, Clara; Baldner, Conrad; Pierro, Antonio
Abstract: This research examined the relationship between individual differences in the tendency towards locomotion (i.e., the aspect of self-regulation concerned with movement from state to state), job search behaviors, and positive employment outcomes (i.e., number of interviews, number of job offers, employment status). Data from two studies with unemployed Italian job seekers found support for a chain reaction towards employment that is initiated by locomotion orientation: individuals who are characterized by high locomotion show more intense job search behavior; as a result, they receive more interviews and job offers, and are more likely to attain employment. These findings are consistent with the literatures on locomotion orientation (Kruglanski, Thompson, Higgins, Atash, Pierro, Shah, & Spiegel, 2000) and job search success (Saks, 2006). Implications for the effect of locomotion orientation on job search success and employment status are discussed. Highlights: In two studies we examined the role of locomotion orientation in job search process and its success. A new antecedent of employment status was investigated from a self-regulatory perspective. Previous research on the effect of job search intensity on job search success criteria was replicated in an Italian sample. Individuals characterized by a high (vs. low) locomotion orientation were more likely to find employment. Locomotion began a "chain reaction" towards employment through increased job search intensity, interviews, and job offers.